POLA USAHATANI LAHAN KERING DENGAN UPAYA KONSERVASI DI DAERAH ALIRAN SUNGAI (DAS) SERAYU WILAYAH KABUPATEN BANYUMAS UPLAND FARMING PATTERN WITH CONSERVATION EFFORT ON SERAYU WATERSHEDS LOCATED IN BANYUMAS REGENCY - N., Dyah Ethika; Sumanto, Bambang; Hastuti, Pudji (Pembangunan Pedesaan, 2005)
This research aimed to calculate cost and revenue farming on Serayu watersheds located in Banyumas Regency on 2003/2004 year, to estimate upland farming index with ruminant husbandry activity; and to estimate factors affecting land conservation by farmer. Sampling method used was two stages cluster random sampling, obtained 13 villages, with 39 respondent of farmer with animal husbandry and 21 one without the husbandry. Result of the research showed that there were seven types of cropping pattern using 3-10 kinds of plant. The lowest cost and revenue were on three kinds of plant and the highest one were on 4 kinds of plant. Farm without the husbandry consisted of seven types of cropping pattern with 29 kinds of plant. The lowest cost and revenue were on 2 kinds of plant and the highest one were on 9 kinds of plant. The amount of cost available and laborpositively affected cropping index significantly for both farming. Cropping value had positive value but had no significant impact to cropping pattern index for both farming. Farm income, number of families on farm, and value of animal ruminant production positively affected conservation activity index but were not affected by amount of family on the farm, land space, formal education, and land owner status.